HSI colour-coded analysis of scattered light of single plasmonic nanoparticles. Issue 22 (19th May 2016) - Zhou, Jun; Lei, Gang; Zheng, Lin Ling; Gao, Peng Fei; Huang, Cheng Zhi
Abstract : An automatical HSI colour-coding method is established for coding dark-field microscopic imaging of single plasmonic nanoparticles (PNPs) showing that the hue value in the HSI colour-coding system is a novel quantitative parameter for chemical and biochemical imaging. Abstract : Single plasmonic nanoparticles (PNPs) analysis with dark-field microscopic imaging (iDFM) has attracted much attention in recent years. The ability for quantitative analysis of iDFM is critical, but cumbersome, for characterizing and analyzing the scattered light of single PNPs. Here, a simple automatic HSI colour coding method is established for coding dark-field microscopic (DFM) images of single PNPs with localized surface plasmon resonance (LSPR) scattered light, showing that hue value in the HSI system can realize accurate quantitative analysis of iDFM and providing a novel approach for quantitative chemical and biochemical imaging at the single nanoparticle level.